An Oncologist’s Dilemma: How to Effectively Eliminate CNS Cancers in Children with Radiation Therapy Whilst Preserving Cognitive Function? - Strickland, Tammy (Trinity Student Medical Journal, 2016)
Cranial irradiation is commonly adopted in the treatment of central nervous system (CNS) tumours, even in younger cancer patients, despite its severe early and late side effects. One of the major consequences of using radiation therapy in the CNS is the inevitable occurrence of normal tissue toxicity and resultant morbidities including cognitive dysfunction, learn- ing impairments and a lower quality of life. These symptoms are in part due to an arrest in the production or survival of neural precursor cells in particular proliferative regions of the brain including the hippocampus. As the population of childhood survivors of CNS or metastatic malignancy grows, more attention must be paid to the debilitating cognitive co-morbidities resulting from radiation therapy in particular. Protective prophylactic pharmaco- logical agents and precise ‘hippocampal-sparing’ radiation techniques should be considered during treatment, while drug or behavioral interventions may be indicated during a patient’s long term follow up period. This brief review overviews radiation therapy uses and mechanisms, investigates some of the currently known cellular and molecular events that lead to functional decline post-irradiation, examines the scarce therapies available to childhood CNS cancer survivors for their long-term cognitive morbidities to date and identifies possible therapeutic niches that could be targeted either during or post-radiation therapy to attenuate its long term consequences in the human brain.